Geotechnical Engineering Unsaturated and Saturated Soils - Briaud, Jean-Louis (Wiley, 2023)
While there are many textbooks on the market that cover geotechnical engineering basics, Geotechnical Engineering: Unsaturated and Saturated Soils, Second Edition is unique in that it is the only textbook available that is rooted within the three phase unsaturated soil mechanics framework. Written by world-renowned, award-winning geotechnical engineering expert Dr. Jean-Louis Briaud, this Second Edition offers the most comprehensive coverage of geotechnical engineering topics on the market from theory to real-world application. This new edition includes new chapters on tunnels, earth dams and embankments, and instrumentation. An all-new case studies chapter features well-known projects such as the Washington Monument, Seattle airport, Eiffel Tower and many more. This edition will include solutions to the end-of-chapter problems. From site investigation and geophysics to earthquake engineering and deep foundations, Geotechnical Engineering is an ideal resource for upper-level undergraduate and graduate courses as well as practicing professionals in geotechnical engineering and soil mechanics.